Tinjauan Hak Konstitusional terhadap Korban Bencana Lumpur Lapindo - Minanda, Evy Flamboyan; Juniati, Tria (Mahkamah Konstitusi Republik Indonesia, 2011)
Events ‘Lapindo Mud’ in Sidoardjo shocked Indonesian society. In the case of this mud volcano, Lapindo allegedly “intentionally save ‘operational costs by not installing casing. When viewed from an economic perspective, the decision affects the installation of the casing to the costs incurred Lapindo. This case has caused harm to residents Siduardjo. This case is just one case, of cases in the field of environmental law that led to disaster for the people of Indonesia. Constitution of the Republic of Indonesia Year 1945 is to include environmental provisions in it, then followed the birth of Law Number 24 Year 2007 on Disaster Management. At the time of this disaster happened, the setting of environmental management regulated in Law Number 23 Year 1997. Are there provisions that already reflects the constitutional rights of disaster victims?Does the presence of the law could meet the challenge? How is its implementation? What about law enforcement?